2021
DOI: 10.1101/2021.08.13.21262021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and safety of inactivated whole virion Coronavirus vaccine with CpG (VLA2001) in healthy adults aged 18 to 55: a randomised phase 1 /2 clinical trial

Abstract: Background We assessed the safety, tolerability and immunogenicity of VLA2001 is a whole-virion inactivated SARS-CoV-2 vaccine adsorbed to alum with a toll-like receptor 9 agonist adjuvant in healthy volunteers aged 18-55. Methods The first 15 participants were enrolled, in groups of 5, to receive two doses, separated by 21 days, of one of three dose concentrations, administered intramuscularly. 138 further participants were randomised 1:1:1 to receive the same 3 dose concentrations, in a double blinded manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Because the recombinant protein vaccines use only a protein fragment of receptor binding domain as the antigen, they may have lower immunogenicity than the whole-pathogen vaccine candidates containing more than 20 immunoreactive epitopes [21,22]. In a randomized phase 1/2 clinical trial with Valneva, antigen-specific interferon-γ T-cells reactive were observed against the spike, membrane, and nucleocapsid proteins [21]. Of course, take into account the fact that not all viral epitopes of the virus need to be immunogenic [23].…”
Section: Discussionmentioning
confidence: 99%
“…Because the recombinant protein vaccines use only a protein fragment of receptor binding domain as the antigen, they may have lower immunogenicity than the whole-pathogen vaccine candidates containing more than 20 immunoreactive epitopes [21,22]. In a randomized phase 1/2 clinical trial with Valneva, antigen-specific interferon-γ T-cells reactive were observed against the spike, membrane, and nucleocapsid proteins [21]. Of course, take into account the fact that not all viral epitopes of the virus need to be immunogenic [23].…”
Section: Discussionmentioning
confidence: 99%
“…After virus propagation, β-propiolactone is used for viral inactivation in order to preserve the native surface structure of the virion, in a robust process that yields high-density and intact Spike protein. 6 Additionally, VLA2001 is adjuvanted with cytosine phospho-guanine (CpG) 1018 and aluminum hydroxide.…”
Section: Methodsmentioning
confidence: 99%
“…The vaccine was exhibited to be safe and well-tolerated and produced both humoral and cellular immune responses, with a clear dose-dependent effect. 34 All samples showed neutralized antibodies against the ancestral virus. The incidence of neutralizing antibodies against Omicron was 87%.…”
Section: Coronavac Vaccinementioning
confidence: 94%
“…The most frequent local reactions were tenderness (58.2%) and pain (41.8%), and systemic reactions included headache (46%) and fatigue (39.2%). The vaccine was exhibited to be safe and well‐tolerated and produced both humoral and cellular immune responses, with a clear dose‐dependent effect 34 . Later, Valneva participated in the Cov‐Boost clinical trial (ISRCTN73765130) to examine seven different COVID‐19 booster vaccines.…”
Section: Vla2001 Vaccinementioning
confidence: 99%
See 1 more Smart Citation